Bioactive Molecules from Extreme Environments II - Giordano, Daniela (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue, as a continuation of the previous Special Issue, "Bioactive Molecules from Extreme Environments" (https://www.mdpi.com/journal/marinedrugs/special_issues/Extreme_Environments accessed on 4 November 2021), includes 10 research articles and 2 reviews, providing a wide overview of the chemical biodiversity offered by different marine organisms inhabiting extreme environments to be used for biotechnological and pharmaceutical applications. The six articles in this Special Issue are focused on the polar regions, which represent an untapped source of marine natural products and are still largely unexplored compared to more accessible sites. Many of these articles refer to Antarctica, which is the coldest and most inaccessible continent on the Earth, where extreme temperatures, light and ice have selected biological communities with a unique suite of bioactive metabolites. The marine organisms of Arctic and Antarctic environments are a reservoir of natural compounds, exhibiting huge structural diversity and significant bioactivities that could be used in human applications.